Records Committee review for rare bird sighting for Eskimo Curlew at Van Buren County before 1907 - Iowa Ornithologists' Union Records Committeeet al (1907)
Records Committee review for Eskimo Curlews at Van Buren County, IA before 1907. Includes a record review document with votes and the original sighting record found in the publication Birds of Iowa by Rudolph Martin Anderson seen by Walter Savage. Epson - sheet feed